Theoretical Aspects of Remote Learning in Grades I–III of the Primary School - Babiarz, Mirosław; Wcześniak, Justyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Early childhood education is an essential stage in the life of every child. Thanks to participation in lessons and school life, the child not only gains knowledge and various skills, but also shapes his personality, establishes bonds, and learns how to function in a social group. At the beginning of March 2020, the current order, also in the field of education, was disrupted by the outbreak of the Covid-19 pandemic. By decision of the state authorities, schools and many other public facilities were closed. Education has changed its current form by moving completely on the virtual plane, which has never happened before. The extremely fast turn of events caused huge chaos in both the pedagogical environment and among parents and their children. This has become a contribution to the theoretical and research considerations of many people.
Keywords: education; distance; learning; help; early education; student